Body, space and pain - Diana M. Torta (Frontiers Research Topics, 2014)
There is growing interest in understanding how the perception of pain (and touch) is influenced by the way we represent our body and the space surrounding it. Recent views argue that pain can only be understood in a larger framework of body perception and action. This attention is driven by accumulating research in experimental and clinical domains, indicating that pain perception depends largely on cognitive factors and multisensory integration. The interest is also boosted by studies on chronic pain conditions suggesting a tight link between body perception and the maintenance of pain. Many aspects remain yet to be elucidated. We welcomed submissions from researchers in cognitive neuroscience and pain to increase our understanding of the interplay among body, space, pain, touch and movement. We aimed to gather insights from different theoretical frameworks and encouraged investigators using a broad range of methods including (but not limited to) behavioural and neuropsychological approaches, imaging techniques, electrophysiology, psychophysiology and TMS to present their results in this Research Topic. In the attempt to go from bench- to bedside we also strongly encouraged submissions from clinicians and physiotherapist whose contribution may help rising some future key questions. Qualitative and phenomenological approaches were also welcome.